Tirosine Kinase Inhibitors Adverse Events. (21st February 2014) - Campiotti, Leonardo; Maresca, Andrea; Guasti, Luigina; Grandi, Anna Maria
Abstract : The authors discuss dasatinib as a tyrosine kinase inhibitor with cardiovascular toxicity, which Lenihan and Kowey did not include in their article "Overview and Management of Cardiac Adverse Events Associated With Tyrosine Kinase Inhibitors."